Ankle and knee stability as predictors for dynamic balance - Bernhardt, V.; Oldham, M. D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The Y-balance test (YBT) is a commonly used clinical tool to predict lower extremity injury risk in athletic populations. Specifically, anterior and posteromedial reach asymmetries of *4 cm have been found to elevate injury risk [1,2]. It is unclear which factors impact YBT dynamic balance. In this study we examined whether muscle mass difference between lower limbs, joint movement during unilateral squat, or static balance during stork balance test were associated with YBT dynamic balance performance.